2014
DOI: 10.5507/bp.2012.038
|View full text |Cite
|
Sign up to set email alerts
|

Valproate activates ERK signaling pathway in primary human hepatocytes

Abstract: Aim. Valproic acid (VPA) is a widely-used anticonvulsant and mood-stabilizing agent. VPA is also known to inhibit histone deacetylases (HDACs) affecting the expression of numerous genes. Methods. In the present study, we examined the effect of VPA on the extracellular signal-related kinase (ERK, p42/p44) pathway (Ras-Raf-MEK-ERK) belonging to the mitogen-activated protein kinases (MAPKs) pathways in primary human hepatocytes. In the liver, the pathway is associated with progression of hepatocellular carcinoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Melatonin is effective in preventing the ischemic brain injury‐induced down‐regulation of Raf‐1, MEK1/2 and ERK1/2 phosphorylation , suggesting that the activation of Raf/MEK/ERK cascade can be mediated by Melatonin. In human hepatocytes, the ERK pathway can be activated by VPA exposure . Given that both melatonin and VPA have been reported to prevent tumor growth and progression in animal models of cancer , it would be interesting to determine the combinatorial effects in vivo in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is effective in preventing the ischemic brain injury‐induced down‐regulation of Raf‐1, MEK1/2 and ERK1/2 phosphorylation , suggesting that the activation of Raf/MEK/ERK cascade can be mediated by Melatonin. In human hepatocytes, the ERK pathway can be activated by VPA exposure . Given that both melatonin and VPA have been reported to prevent tumor growth and progression in animal models of cancer , it would be interesting to determine the combinatorial effects in vivo in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the CNS, a paucity of information has been available to link VPA with ERK-activity in the liver. Thus, by far, only one in vitro study reported that VPA activates ERK phosphorylation in primary human hepatocytes, a response that was mimicked by HDAC inhibitor, trichostatin-A ( Bitman et al, 2014 ), implying that HDAC inhibition is a primary stimulus for ERK in human hepatocytes. However, this this study has not looked at role of oxidative stress or VPA metabolites, possibly due to limited biologic windows within a cell culture setup.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that CYP1A1 can be active in catalyzing the formation of ROS The previous reports have suggested that Nrf2-dependent transcription may be facilitated by the MAPK pathway such as ERK, JNK, and p38 (Eggler et al, 2008;Zhai et al, 2013), which were activated by VPA (Einat et al, 2003;Xie et al, 2010;Yamauchi et al, 2010). However, Bitman et al (2014) reported that the effect of VPA on MAPK pathways are different for different cell lines. Thus, we studied the phosphorylation of the ERK, JNK, and p38 pathways by VPA in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 97%
“…However, Bitman et al. (2014) reported that the effect of VPA on MAPK pathways are different for different cell lines. Thus, we studied the phosphorylation of the ERK, JNK, and p38 pathways by VPA in Caco‐2 cells.…”
Section: Discussionmentioning
confidence: 99%